(untitled) (Swiss Medical Weekly, 2011)
Vitamin D is important for bone metabolism and neuromuscular function. While a routine dosage is often proposed in osteoporotic patients, it is not so evident in rheumatology outpatients where it has been shown that the prevalence of hypovitaminosis D is high. The aim of the current study was to systematically evaluate the vitamin D status in our outpatient rheumatology population to define the severity of the problem according to rheumatologic diseases. During November 2009, all patients were offered a screening test for 25-OH vitamin D levels and categorised as deficient (<10 µg/l [ng/ml] [25 nmol/l]), insufficient (10 µg/l to 30 µg/l [25 to 75 nmol/l]) or normal (>30 µg/l [75 nmol/l]). A total of 272 patients were included. The mean 25-OH vitamin D level was 21 µg/l (range 1.5 to 45.9). A total of 20 patients had vitamin D deficiency, 215 patients had an insufficiency and 37 patients had normal results. In the group of patients with osteoporosis mean level of 25-OH vitamin D was 25 µg/l and 31% had normal results. In patients with inflammatory rheumatic diseases (N = 219), the mean level of 25-OH vitamin D was 20.5 µg/l, and only 12% had normal 25-OH vitamin D levels.In the small group of patients with degenerative disease (N = 33), the mean level of 25-OH vitamin D was 21.8 µg/l, and 21% had normal results. Insufficiency and deficiency were even seen in 38% of the patients who were taking supplements. These results confirm that hypovitaminosis D is highly prevalent in an outpatient population of rheumatology patients, affecting 86% of subjects.Despite oral supplementation (taken in 38% of our population), only a quarter of those on oral supplementation attained normal values of 25-OH vitamin D.